Creative chaos in Spain before the Arab Islamic conquest (Texas Journal of Multidisciplinary Studies, 2025)
The Arab conquest of Spain was the first entry of the Arabs into the European continent, and it is considered a major transformation in Islamic history in general, and Spanish history in particular, as Spain suffered under the rule of the Goths from instability and reassurance, as their rule of Spain was characterized by devastation and destruction, due to their persecution of the rest of the population of Spain, as Spanish society began to complain of chaos and instability in various areas of life, which led to the continuation of disobedience and conspiracies carried out by the nobles in order to seize the throne and separate from the Visigothic Kingdom, which led to the prevalence of weakness among the Goths, in addition to the desire of the Spanish people who were exposed to persecution by the Church, to change and improve their situation by seeking help from external forces, so they leaned towards the Arabs because of their desire to get rid of what they were in on the one hand, and on the other hand because of what the Arabs were distinguished by in terms of justice, tolerance and equality.